2016
DOI: 10.1002/ajoc.201500526
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Covalent Grafting of Tripod‐Shaped Oligo(p‐phenylene)s End‐Capped with Azide Groups

Abstract: Here we report the synthesis and characterization of several tripod-shaped oligo(p-phenylene)s molecules with legs composed of five and three phenylene units, compounds 1 and 2,r espectively.I nt heses tructures, each leg is end-capped with an azide group andt he terminal functional arm contains an acetylene or bromine group. The presented synthesis has as the key step aP d-catalyzedS uzukic rosscoupling reaction. In particular,t he iodine derivative from the silicon core molecule reacts with the appropriate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…27 Despite this, and since we have previously obtained good results for the attachment of a small tripod (three phenylene units) on alkynyl modified silicon surfaces, in this work we initially prepared the penta(p-phenylene) modified surfaces by following the same procedure. 20 The clickable silicon surfaces were prepared by photo-activated hydrosilylation reaction of the alkene derivative 3 onto H-Si(111) substrates (Surface A in Scheme 1). 28 Then, tripod 1-modified silicon surfaces were prepared by CuAAC reaction onto the previously prepared surfaces in presence of 1, a copper source and a base (Surface B in Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Despite this, and since we have previously obtained good results for the attachment of a small tripod (three phenylene units) on alkynyl modified silicon surfaces, in this work we initially prepared the penta(p-phenylene) modified surfaces by following the same procedure. 20 The clickable silicon surfaces were prepared by photo-activated hydrosilylation reaction of the alkene derivative 3 onto H-Si(111) substrates (Surface A in Scheme 1). 28 Then, tripod 1-modified silicon surfaces were prepared by CuAAC reaction onto the previously prepared surfaces in presence of 1, a copper source and a base (Surface B in Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…28 Tripod 1 was synthesized by Suzuki-coupling of corresponding boron esters, according to the published procedures. 20,25 Tetrahydrofuran (THF) was dried and distilled from sodium benzophenone under an argon atmosphere, and dichloromethane was dried and distilled from CaH2 under an argon atmosphere. Millipore water was used when needed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of tripodal compound 1 . Under argon atmosphere, compound 11 [58a] (422 mg, 0.53 mmol), compound 3 (780 mg, 1.60 mmol), Pd(PPh 3 ) 4 (368 mg, 0.318 mmol) and AgCO 3 (1.0 g, 4.24 mmol) were dissolved in dry THF. The mixture was stirred under argon atmosphere at 20 °C for 12 h. After this period, the reaction mixture was filtered through celite, washed with several portions of CH 2 Cl 2 and the solvent was removed under vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…58,59 We and others have reported the photo-activated graing of the a-OEG-u-alkenes onto hydrogen-terminated silicon, forming OEG-terminated monolayers that are directly bound to the silicon substrate via Si-C bonds (Scheme 1). 13,40,48,51,[60][61][62][63][64][65][66][67][68][69][70][71][72] We performed this process in a simple apparatus combining a Schlenk tube with a quartz cell at a low vacuum level, 68,69,73,74 using OEG-terminated alkenes C 11 EG n (n ¼ 3, 6, 7 and 9). We found that C 11 EG n with n $ 6 led to lms that reduced the adsorption of brinogen to $3% monolayer aer immersion in brinogen (1 mg mL À1 ) for 1 h and brief washing with water.…”
Section: Introductionmentioning
confidence: 99%